Face à condição da Arquitectura. Quinta do Freixo: percurso e projecto - Ricardo Jorge da Costa Fernandes da Silva Nunes (2019)
After five years of university studies and after a period of approximately two years practicing the professional exercise of architecture, shared between Spain and Portugal, it seemed to me essencial to explore a path capable of comunicating and clarifying an idea constantly linked to the professional, social and civilian activity of an architect - facing the condition in Architecture. Through the opportunity given to me, in order to explore the study that I present here, I expose what I believe to be a journey through a real and concrete architecture project, of which I consider being part, in order to achieve, through it, a range of insights, motives and specific circumstances, capable of characterizing that confrontation with the condition. The report, presented here, digests a period of drafting process that began in January 2018, four months after I joined the working group at Atelier da Costa. The written texts, born in distinct moments, are self proposed reflections, some times scattered, capable of translating a possible definition for a personal understanding about architecture and its constraints. The topics mix, communicate, and clarify, and, in an open way, a drafting process. Through this exposition, and a result of an overall view, it's intended to explain a set of interpretations, that are still open to new and different readings. With the use of drawing, we try to present a state of play. Alongside this moment of reflection, the project goes ahead, through an intense process and in constant activity. Along with all of this, we try to witness a joint performance between the student and the architecture professional. Through a personal record, we try to communicate the inherent dymamic of the activity of making architecture. An autounomous, real and revealing reflection, under the eyes of a student-professional that relives his condition, with the conscious importance of his work context, capable of influencing his experiences for the future.